2010 IEEE 21st International Symposium on Software Reliability Engineering 2010
DOI: 10.1109/issre.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Is Data Privacy Always Good for Software Testing?

Abstract: Abstract-Database-centric applications (DCAs) are common in enterprise computing, and they use nontrivial databases. Testing of DCAs is increasingly outsourced to test centers in order to achieve lower cost and higher quality. When releasing proprietary DCAs, its databases should also be made available to test engineers, so that they can test using real data. Testing with real data is important, since fake data lacks many of the intricate semantic connections among the original data elements. However, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Grechanik et al [23] found that kanonymity greatly degraded the test-coverage of data-centric applications. Furthermore, Brickell and Shmatikov [6] report experiments where to achieve privacy using the above methods "requires almost complete destruction of the data mining capability".…”
Section: Problems With Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…Grechanik et al [23] found that kanonymity greatly degraded the test-coverage of data-centric applications. Furthermore, Brickell and Shmatikov [6] report experiments where to achieve privacy using the above methods "requires almost complete destruction of the data mining capability".…”
Section: Problems With Privacymentioning
confidence: 99%
“…Since Grenchanik et al and Brickell and Shmatikov [6], [23] report that k-anonymity, l-diversity, and t-closeness damage the utility of a data-set, we elect to use another privacy algorithm.…”
Section: A Data Swappingmentioning
confidence: 99%
“…Grechanik et al [5] found that k-anonymity greatly degraded the test coverage of datacentric applications. Furthermore, Brickell and Shmatikov [6] reported experiments where achieving privacy using the above methods "requires almost complete destruction of the data mining capability."…”
Section: Problems With Privacymentioning
confidence: 99%
“…The result of this is shown in Table 2b. For example, the attribute values of wmc are replaced by two subranges of values ( [3][4][5][6] and (6)(7)(8)(9)(10)(11)(12)(13)(14)). Here, all values from 3 to 6 inclusive are placed in the first subrange and all values between 6 and 14 (not including 6) are placed in the last subrange.…”
Section: Example Of Cliff+morphmentioning
confidence: 99%
See 1 more Smart Citation